Analisis Fundraising Melalui Unit Pengumpul Zakat: Mengukur Minat Berdonasi - Harahap, Muhammad Arfan; Hasibuan, Sri Wahyuni; Daud, Ahmad (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Fundraising activities through zakat collection units still have problems and need to be analyzed. This research aims to measure the interest in donating through the Zakat Collecting Unit of STAI Jam’iyah Mahmudiyah, Langkat (UPZ STAI-JM). To analyze research data, which is a latent variable, it is carried out using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method with the help of the SmartPls 4.0 tool. The research sample of 100 respondents provided data via a questionnaire which was distributed directly. The results of the study revealed that the interest in donating through UPZ STAI-JM was influenced by the variables of trust, income, and convenience by 71.4%. Where the trust variable gives the strongest influence and is followed by the income variable on the interest in donating. Meanwhile, the convenience variable does not influence the interest in donating.